TECHNOLOGY ADOPTION USING MEDICAL IMAGE PROCESSING TOOLS IN GLOBAL HEALTH SECTOR DEVELOPMENT - Venkatesh Jaganathan; Thenmozhi Srinivasan; Balasubramanie Palanisamy; Priyesh Cherurveettil; Aarthy Chellasamy; T. Suganthalakshmi (European Scientific Journal, ESJ, 2014)
Medical Imaging is a major development in the field of medicine for past 100 years. The tool helps the physicians not only to detect the diseases but also the intensity of the disease can be captured. The paper discusses about the prevailing health system and insurance schemes, the treatment facilities for disease like cancer. The availability of medical imaging tools like x-ray, mammogram, ultrasound, CT and MRI scans and its innovations for the public health diagnosis the diseases in various methods with the aid of modern machines and techniques. The techniques vary in terms of cost, methodology in detecting the diseases and even the accuracy. The people could not continue the treatment because of high cost and sometimes scarcity of medicines. As the treatment are costlier irrespective of various classes of people approach the social security organizations and because of continuous usage the equipments worn out. Though these tools are considered as boon in the field of medical imaging each has its own drawback. The result of the paper states that the physicians can detect the early stage of disease with the aid of these tools and can come up with treatment that will avoid serious health issues or sometimes death. Also the government of concern country is responsible for all the public and seek opportunity for developing health sector often.